Design and Validation of Canvas-Based Interactive General Biology Modules: Scientific Literacy Scaffolds within Project-Based Learning to Support 4C Skills - Nana Sutrisna; Dwitri Pilendia (Yayasan Nurul Yakin Bunga Tanjung, 2026)
The Society 5.0 era calls for learning innovations that support both content understanding and 21st-century competencies, particularly the 4C skills (communication, collaboration, critical thinking, and creativity). This study designed and validated Canvas-based interactive General Biology modules by embedding scientific literacy scaffolds within Project-Based Learning (PjBL) phases to support students’ 4C-related skills. The development followed Plomp’s model (preliminary research, prototyping, and assessment) and involved 25 purposively selected students at STKIP Muhammadiyah Sungai Penuh. The integration mechanism was operationalized by mapping scientific literacy components (e.g., interpreting scientific information, evaluating evidence, and scientific reasoning) into each PjBL phase and implementing them through Canvas features such as structured Modules, staged Assignments, Rubrics, Discussions/Groups, and feedback tools. Data were collected using validity and practicality questionnaires, checklists, and interviews. Results indicated that the modules met the criteria for validity (mean score 87.55, valid) and practicality based on lecturer and student responses (scores 84.25 and 84.89, practical). A limited tryout produced N-Gain indicators suggesting promising 4C-related improvement (communication 0.75, collaboration 0.75, critical thinking 0.78, creativity 0.74), but generalizability is limited due to the small, single-institution sample.